Academic Word List Pronunciation of the First Year English Education Students - Jati Landhung History; Barli Bram (VELES Voices of English Language Education Society, 2019)
Pronunciation has been one of the compulsory courses for the first year English education students of Sanata Dharma University, Yogyakarta. Considering the importance of pronunciation skills for the English students, the researchers conducted research to investigate capability of the first year English Education students in pronouncing academic words listed in the Academic Word List. This study aimed to examine whether, firstly, the first year English Education students of Sanata Dharma University pronounced the selected academic words correctly and secondly, to discover the percentage of the correct pronunciation of the students in pronouncing the academic words. Data, consisting of pronunciations of 10 selected academic words, were collected through audio recordings. To solve the first question, the researchers conducted a one-shot design study, namely dealing with the pronunciation performance of the students at a particular time. To resolve the second question, the researchers calculated the percentage of the students’ correct pronunciations. Results showed that as a whole the students mispronounced the selected academic words and the percentage of correct pronunciation reached 35 per cent.